Global chaos synchronization of new chaotic system using linear active control - Ahmad, Israr; Saaban, Azizan; Ibrahim, Adyda; Shahzad, Mohammad (Wiley Periodicals, Inc., 2014)
Chaos synchronization is a procedure where one chaotic oscillator is forced to adjust the properties of another chaotic oscillator for all future states.This research paper studies and investigates the global chaos synchronization problem of two identical chaotic systems and two non-identical chaotic systems using the linear active control technique.Based on the Lyapunov stability theory and using the linear active control technique, the stabilizing controllers are designed for asymptotically global stability of the closed-loop system for both identical and non-identical synchronization.Numerical simulations and graphs are imparted to justify the efficiency and effectiveness of the proposed scheme.All simulations have been done by using mathematica 9. © 2014 Wiley Periodicals, Inc. Complexity, 2014